The amphiregulin/EGFR axis has limited contribution in controlling autoimmune diabetes - Arielle Raugh; Yi Jing; Matthew L. Bettini; Maria Bettini (Scientific Reports, 2023)
Abstract Conventional immunosuppressive functions of CD4+Foxp3+ regulatory T cells (Tregs) in type 1 diabetes (T1D) pathogenesis have been well described, but whether Tregs have additional non-immunological functions supporting tissue homeostasis in pancreatic islets is unknown. Within the last decade novel tissue repair functions have been ascribed to Tregs. One function is production of the epidermal growth factor receptor (EGFR) ligand, amphiregulin, which promotes tissue repair in response to inflammatory or mechanical tissue injury. However, whether such pathways are engaged during autoimmune diabetes and promote tissue repair is undetermined. Previously, we observed that upregulation of amphiregulin at the transcriptional level was associated with functional Treg populations in the non-obese diabetic (NOD) mouse model of T1D. From this we postulated that amphiregulin promoted islet tissue repair and slowed the progression of diabetes in NOD mice. Here, we report that islet-infiltrating Tregs have increased capacity to produce amphiregulin, and that both Tregs and beta cells express EGFR. Moreover, we show that amphiregulin can directly modulate mediators of endoplasmic reticulum stress in beta cells. Despite this, NOD amphiregulin deficient mice showed no acceleration of spontaneous autoimmune diabetes. Taken together, the data suggest that the ability for amphiregulin to affect the progression of autoimmune diabetes is limited.